Sex differences in the efficacy, safety and persistence of patients with psoriatic arthritis treated with tofacitinib: a post-hoc analysis of phase 3 trials and long-term extension - Dafna D Gladman; Lihi Eder; Vibeke Strand; David Gruben; Alexis Ogdie; Ari Polachek; Philip Mease; Sibel Z Aydin; Cassandra Kinch; Remy A Pollock; Rayana Luna; Mary Jane Cadatal (RMD Open, 2023)
Background Evaluate the impact of sex on tofacitinib efficacy, safety and persistence (time to discontinuation) in patients with psoriatic arthritis (PsA).Methods Data were pooled from two phase 3 randomised controlled trials. Patients were randomised to tofacitinib 5 mg or 10 mg two times per day, adalimumab 40 mg every 2 weeks or placebo. Efficacy outcomes to month 12 included American College of Rheumatology (ACR)20/50/70, minimal disease activity (MDA), Psoriasis Area Severity Index (PASI)75, change from baseline (∆) in Health Assessment Questionnaire-Disability Index (HAQ-DI) and ∆Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F). Safety was assessed to month 12 and persistence was assessed to month 42 of a long-term extension study.Results Overall, 816 patients were included (54.3% females). At baseline, higher tender joint counts, enthesitis scores and worse HAQ-DI and FACIT-F were reported in females versus males; presence of dactylitis and PASI were greater in males versus females. At month 3, tofacitinib efficacy generally exceeded placebo in both sexes. Overall, similar ACR20/50/70, PASI75, ∆HAQ-DI and ∆FACIT-F were observed for tofacitinib between sexes; females were less likely to achieve MDA. Similar proportions of males/females receiving tofacitinib (both doses) experienced treatment-emergent adverse events (AEs). Serious AEs occurred in 3.4%/6.6% and 4.0%/5.9% males/females with tofacitinib 5 mg and 10 mg two times per day. Persistence was generally similar between sexes.Conclusion Tofacitinib efficacy exceeded placebo in both sexes and was comparable between sexes. Consistent with previous studies of PsA treatments, females were less likely to achieve MDA, likely due to baseline differences. Safety and time to discontinuation were generally similar between sexes.Trial registration number NCT01877668; NCT01882439; NCT01976364.